Behind the gates : life, security, and the pursuit of happiness in fortress America - Low, Setha M. (Routledge, 2003)
"Gated communities are the fastest growing form of housing in the United States. In the last twenty years, thousands upon thousands of upper- and middle-class Americans have retreated into these exclusive neighborhoods. What has sparked this alarming trend?" "Behind the Gates is an account of what life is like in these suburban fortresses." "In this account, Setha Low probes the hopes, dreams, and fears of gated community residents to uncover how the rapid growth of fortress neighborhoods is effecting subtle transformations in American middle-class values."--Jacket